2011
DOI: 10.1002/clc.20831
|View full text |Cite
|
Sign up to set email alerts
|

Renal Dysfunction in Heart Failure Is Due to Congestion but Not Low Output

Abstract: Background: Renal dysfunction in heart failure is thought to be due to poor perfusion of the kidney. Hypothesis: We tested the hypothesis that passive congestion is more important than poor perfusion. Methods: We retrospectively studied the data on 178 patients who underwent right heart catheterization for evaluation of heart failure and had serum creatinine (Cr) measured on the same day. Results: Serum Cr and glomerular filtration rate (GFR) correlated with central venous pressure (r = 0.22, P = 0.001 and r =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
56
0
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 10 publications
4
56
0
5
Order By: Relevance
“…Moreover, high central venous pressure correlated with low estimated GFR in a study by Damman et al [16], and could predict mortality, independent of the cardiac index. These findings were confirmed by Guglin et al [17] who found that low estimated GFR was associated with elevated central venous pressure, but not cardiac index or left ventricular ejection fraction. It has been challenging to reconcile these findings with the existing literature supporting a primary role for cardiac output in maintaining renal perfusion and function.…”
Section: Emerging Concepts In Cardiorenal Pathophysiology: Renal Venosupporting
confidence: 70%
“…Moreover, high central venous pressure correlated with low estimated GFR in a study by Damman et al [16], and could predict mortality, independent of the cardiac index. These findings were confirmed by Guglin et al [17] who found that low estimated GFR was associated with elevated central venous pressure, but not cardiac index or left ventricular ejection fraction. It has been challenging to reconcile these findings with the existing literature supporting a primary role for cardiac output in maintaining renal perfusion and function.…”
Section: Emerging Concepts In Cardiorenal Pathophysiology: Renal Venosupporting
confidence: 70%
“…However, it is often not feasible to serially repeat invasive catherization. We therefore chose to follow the majority of the literature and pursue a cross-sectional study where the utilization of a large number of data points taken from patients at different phases in heart failure can elicit these trends [9, 10, 15]. …”
Section: Discussionmentioning
confidence: 99%
“…Those that do are often small in size. Some analyses from the ESCAPE trial have suggested no association between renal failure and any pulmonary artery catherization hemodynamic value [8, 13], whilst other observational series suggest weak associations between renal failure and cardiac congestion [7, 9, 10, 14, 15]. Damman et al [15] demonstrated in the largest series on this topic by far ( n = 2,557 patients) an inverse relationship in terms of cardiac filling pressures, predominantly renal artery pressure, with renal function.…”
Section: Introductionmentioning
confidence: 99%
“…Damman et al reported that high central venous pressure (CVP) correlated with low estimated GFR (eGFR) and could predict mortality independent of the cardiac index in HF patients (32). Similarly, Guglin et al found that low eGFR was associated with elevated CVP but not with cardiac index or left ventricular ejection fraction in these patients (33). A primary role of venous congestion in ADHF and cardiorenal syndrome is especially appealing because it could potentially be amenable to fluid removal by UF.…”
Section: Venous Decongestionmentioning
confidence: 99%